Artificial Intelligence and Risk Reduction in Supply Chain Management (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Supply chain management faces unprecedented challenges from global disruptions, geopolitical instability, and increasing complexity in interconnected networks. Artificial Intelligence (AI) has emerged as a transformative technology for mitigating supply chain risks through predictive analytics, real-time monitoring, and autonomous decision-making capabilities. This paper examines the role of AI in reducing supply chain risks, exploring key AI technologies including machine learning algorithms, neural networks, digital twins, and blockchain integration. Through systematic analysis of recent literature and industry case studies, this research demonstrates that AI-driven solutions enhance risk prediction accuracy by 20–50%, improve response times by 30–40%, and enable proactive disruption management. The study categorizes supply chain risks into internal (manufacturing, planning, business) and external (demand, environmental, geopolitical, cybersecurity) types, and analyzes how specific AI techniques address each category. Key findings indicate that Random Forest, XGBoost, and deep learning models significantly outperform traditional statistical methods in forecasting disruptions. Real-world implementations by Amazon, UPS, FedEx, and Unilever validate AI's effectiveness in optimizing inventory allocation, route planning, and supplier risk assessment. This research contributes to the growing body of knowledge on AI-enabled supply chain resilience and provides practical insights for organizations seeking to implement intelligent risk management systems. Future research directions include explainable AI (XAI) for transparent decision-making, integration with IoT sensors for enhanced visibility, and development of adaptive algorithms for dynamic risk environments.